2018
DOI: 10.1080/10967494.2018.1467987
|View full text |Cite
|
Sign up to set email alerts
|

Stages and Determinants of E-Government Development: A Twelve-Year Longitudinal Study of Global Cities

Abstract: Global e-government innovations are at the forefront of municipal efforts to be better organized and more efficient in delivering services and improving outcomes for the public. Scholars have argued that such innovations are embedded in institutional and environmental factors, and municipal e-government growth evolves through stages as a result of the effects of these factors. However, existing studies rarely model the distinct success factors of the different stages. This article addresses that shortcoming wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 73 publications
5
37
0
4
Order By: Relevance
“…Specific variables can drive e-government growth phases, and it is show that egovernment phases are largely driven by standard. There is a positive association between population size, GDP and regional competition become one of it points (Ingrams, Manoharan, Schmidthuber, & Holzer, 2018). While Rokhman (2016) founds that un-integrated policy and unclear procedures are the main problems that government need to focus on (Rokhman, 2016).…”
Section: Theoritical Framework Electronic Government As a Discoursementioning
confidence: 99%
“…Specific variables can drive e-government growth phases, and it is show that egovernment phases are largely driven by standard. There is a positive association between population size, GDP and regional competition become one of it points (Ingrams, Manoharan, Schmidthuber, & Holzer, 2018). While Rokhman (2016) founds that un-integrated policy and unclear procedures are the main problems that government need to focus on (Rokhman, 2016).…”
Section: Theoritical Framework Electronic Government As a Discoursementioning
confidence: 99%
“…The development of e-government and the availability of needed datasets have incited scholars to focus on many topics linked to egovernment. Some of them studied the determinants of e-government implementation [6], [7], while others dealt with barriers and challenges to the expansion of e-government [8], [9] and finally the economic and societal effects of e-government [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, e-Government development implementation is measured through stages which then produce determinants (Layne & Lee, 2001;Moon & Norris, 2005;Rahman et al, 2014;Bayona & Morales, 2018, Siau & Long, 2005. These determinants include financial resources and Gross Domestic Product (GDP); socio-economic factors, such as wealth, level of education, and technology access; and political factors, including the significant role of elected officials in e-government initiation (Manoharan 2013;Ingrams et al,2018). Studies have shown how economic and technological factors have a positive and significant relationship on the development of e-government at the national level (Domínguez, et al 2011;Moon & Norris, 2005).…”
Section: Introductionmentioning
confidence: 99%